Kinematics of M-type giant semi-regular variables from the Hipparcos catalogue - Aslan, Zeki; Yeşilyaprak, Cahit (CSIRO PUBLISHING, 150 OXFORD ST, PO BOX 1139, COLLINGWOOD, VICTORIA 3066, AUSTRALIA, 2008)
The kinematics of M-type (O-rich) giant semi- regular (SR) variable stars were examined. They were grouped with respect to their relative parallax errors (epsilon(pi)/pi) in order to study the stars having relatively better parallax, and with the period limit (70 d). The spatial and velocity distributions were examined and the results were compared with the results of irregular (L) and Mira-type variables. It was found that M- type giant SR variables are distributed similarly to thin-disc stars and form a kinematically homogeneous group. When the kinematic properties of M- type giant SR variables were compared with those of L- and Mira-type variables, it was estimated that M- type giant SR variables behave as old-disc objects and their kinematic ages vary approximately between 2 and 9 Gyr.
Keywords: stars : distances; stars : late-type; stars : kinematics; stars : evolution; amplitude red variables; long-period variables; semiregular variables; branch stars; parallaxes; mira; metallicity; mode; multiperiodicity; systems; yıldız: mesafeleri; yıldız: Geç tip; yıldız: kinematiği; yıldız: evrim; genlik kırmızı değişkenler; uzun süre değişkenleri; yarı düzenli değişkenleri; şube yıldız; paralakslarda; metallilik; kip; sistemler; çok dönemsellik